2011
DOI: 10.1523/jneurosci.2725-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Processing in the Human Language System: Synergy between the Arcuate Fascicle and Extreme Capsule

Abstract: The production and comprehension of human language is thought to involve a network of frontal, parietal, and temporal cortical loci interconnected by two dominant white matter pathways. These two white matter bundles, often referred to as the dorsal and ventral processing tracts, are hypothesized to have markedly different language functions. The dorsal tract is thought to process phonological processing, while the ventral tract is considered to abet semantics. This proposed functional differentiation of tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
89
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 32 publications
6
89
1
2
Order By: Relevance
“…Importantly, whole-brain correlations showed that only performance on tasks loading strongly on either phonology or semantics fit into this dual-stream model, whereas complex linguistic functions of syntax and morphology required integrity of both pathways (Rolheiser, et al, 2011).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Importantly, whole-brain correlations showed that only performance on tasks loading strongly on either phonology or semantics fit into this dual-stream model, whereas complex linguistic functions of syntax and morphology required integrity of both pathways (Rolheiser, et al, 2011).…”
mentioning
confidence: 90%
“…The dorsal stream, on the other hand, is proposed to be strongly lefthemisphere dominant (Berthier, Lambon Ralph, Pujol, & Green, 2012;Catani & Mesulam, 2008) Although independent, the ventral and dorsal streams are highly interactive. Rolheiser, Stamatakis and Tyler (2011) considered 24 chronic stroke patients' performance across 10 tests involving key aspects of language production and comprehension and how this related to the results of diffusion weighted imaging. Phonological processing was found to load most heavily on the arcuate fascicle, implicated in the dorsal stream (Hickok & Poeppel, 2007).…”
mentioning
confidence: 99%
“…Whereas the dorsal pathway, encompassing parietal lobe, superior temporal gyrus (STG) and inferior frontal gyrus (IFG) pars opercularis, is thought to subserve phonological processing, the ventral pathway, including vOT and anterior IFG regions (i.e., pars triangularis and pars obitalis), supports mapping of orthographic-lexical stimuli onto semantic representations (Sandak et al 2004). These findings have also been bolstered by studies looking at white-matter pathways (Saur et al 2008;Rolheiser et al 2011;Friederici, 2012). Although results in studies with monolingual samples show a differential engagement of dorsal versus ventral reading regions, there is limited evidence as to what extent similar functional involvement of these networks is present in bilingual reading, and which aspects of reading (e.g., direct phonology versus assembled phonology) modulate their recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…1C) is a fiber tract that connects the posterior inferior frontal cortex, including Broca's area, and the lateral temporal cortex, including Wernicke's area. This pathway is important for phonological awareness, an essential skill in reading development (6,24,25). The ILF (orange in Fig.…”
mentioning
confidence: 99%